CHARACTERIZATION OF PHYSICO-CHEMICAL ATTRIBUTES OF LITCHI FRUIT AND ITS RELATION WITH FRUIT SKIN CRACKING - I.U. Haq; A. Rab (Journal of Animal and Plant Sciences, 2012)
The study on characterization of physico-chemical attributes of litchi fruit and its relation with fruit skin cracking was conducted to evaluate litchi cultivars for fruit quality attributes such as fruit size, fruit weight, pulp weight, TSS, total sugars, fruit cracking, fruit specific gravity, reducing and non reducing sugars, skin strength and its boron and calcium content. There were no significant difference in plant age group 10 and 20 years except skin strength and skin calcium content but litchi cultivars varied significantly for most of the studied parameters. Cultivar Gola with fruit weight (23.08g), pulp weight (16.58g), TSS (22.13%) and total sugars (21.57%) was significantly superior in quality attributes but also had the maximum fruit cracking (43.50%) than the rest of the cultivars. Cultivar Gola also had the highest reducing sugars (17.98%) and specific gravity (1.092) but the least non reducing sugars (3.59%) amongst the cultivars under study while cultivar Bedana had the least reducing sugar (5.67%) and specific gravity (1.031) but the most non reducing sugars (9.76%). Skin strength (3.26 kg cm-2) and boron content (0.12 mg/100g DW) were highest in cultivar Bedana, while the highest calcium content was in cultivar Surahi (5.00 mg/100g DW).
Keywords: Litchi; Cultivars; Fruit Quality; Cracking; Calcium; Boron